Intention to personal computing among secondary school teachers in Malaysia: A case shaped by the technology acceptance model - Ramayah, T.; Ibarahim, Amlus; Ignatius, Joshua (2004)
With the recent emphasis in the development of a knowledge based society, this paper provides a springboard by assessing the preponderance of secondary school teachers in personal computing through the application of Technology Acceptance Model (TAM). Chiefly, two main constructs of perceived ease of use (PEU) and perceived usefulness (PU) were used for the said purpose—in combination with 1915 responses gathered from a nationwide mail survey consisting of the 12 states in Peninsular Malaysia. The survey instrument was validated through Principal component factor analysis prior to investigating both, i.e. the relationship between PEU and PU towards the intention to use. PEU was found to have a strong influence on PU. However, it was discovered that PU exerted a stronger influence than PEU in explaining Personal Computer (PC) usage intention. This suggests that PC has to be continually perceived as useful to be used in the long run, while its ease of use is important in promoting initial usage. Implications for policy makers in the education sector are explored further.